Mexico : Can Mobile Tutors Improve Learning in Remote Schools? - Agostinelli, Francesco; Avitabile, Ciro; Bobba, Matteo; Sanchez, Alonso (World Bank, Washington, DC, 2020)
Achieving inclusive and quality education for all is a global priority, and policymakers are still grappling with the best ways to ensure the poorest and most marginalized children are in school and learning. About 120 million children, many from rural areas, are still out of school, despite a recent global push for universal access to education. Even when they stay in school, children from poor, rural areas often show the lowest gains in learning. Recruiting and retaining teachers to work in remote areas is a major challenge, and many low and middle-income countries rely on members of the community to teach local schools.